Traditional Market Design in Transit Oriented Development Area (TOD) in Pinang Baris - Achmad Delianur Nasution; Mega Ratu Pertiwi (Talenta Publisher, 2017)
According to the development plan of MEBIDANGRO, there are 21 modes of transportation in the future carried out repairs and revitalization, one of which is Pinang Baris Transit Oriented Development (TOD). The TOD Pinang Baris design integrates the Bus Terminal Pinang Baris with other building functions as a support, with sky bridge and pedestrian aimed at realizing a pedestrian-friendly and vehicle-free TOD region. One function of the building within the TOD Pinang Baris is the Traditional Market. Traditional Market is chosen to be a building that serves as a business center in the TOD area whose design is suitable for the behavior of users in the Market. Based on the analysis, The Traditional Market is designed on 2.5 hectares of land, with a building area of 16.802 m2, and the number of floors is 3 floors. General problems in the market such as hot, stuffy, smelly and wasteful use of electrical energy in traditional market solved by applying Green Architecture themes such as the design of skylights and voids providing natural lighting to conserve electricity and cross ventilation to keep it stuffy. Similarly, the inconvenience of building users in the market to the circulation that is difficult to access, then the design is applied circle circulation concept so that there are no more kiosks and loods that are isolated from the visitors. Therefore, thus, the implementation of green architectural themes in traditional markets can meet the needs and convenience of its user.